1986
DOI: 10.1139/v86-270
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic solvent effects on acid-catalyzed hydrolysis of sucrose in aqueous mixtures of some protic, aprotic, and dipolar aprotic solvents

Abstract: URMILA MANDAL, KAUSHIK DAS, and KIRON KUMAR KUNDU. Can. J. Chem. 64, 1638 (1986). Rate constants of acid-catalyzed hydrolysis of sucrose (S) to D-glucose and L-fructose have been determined at 25OC by optical rotation measurements in aqueous mixtures of protophobic protic glycerol (GL), protophilic protic urea (UH), aprotic dioxane (D), and dipolar aprotic dimethyl sulphoxide (DMSO). Transfer free energies of the substrate sucrose, AG(S) have also been determined in the solvents from solubility measurements. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Aqueous acidified sucrose has been shown to undergo specific acid catalyzed hydrolysis. Mandal et al (1986) found that the kinetic behavior of acid-catalyzed sucrose hydrolysis in four nonprotic solvents was similar to that in water and therefore assumed specific acid catalysis. Lo ¨nnberg and Gyle ´n (1983) found the rate-limiting step in hydrolysis of alkyl fructofuranosides to be the formation of the fructosyl carbocation and not the protonation of the glycosidic oxygen.…”
Section: Resultsmentioning
confidence: 96%
“…Aqueous acidified sucrose has been shown to undergo specific acid catalyzed hydrolysis. Mandal et al (1986) found that the kinetic behavior of acid-catalyzed sucrose hydrolysis in four nonprotic solvents was similar to that in water and therefore assumed specific acid catalysis. Lo ¨nnberg and Gyle ´n (1983) found the rate-limiting step in hydrolysis of alkyl fructofuranosides to be the formation of the fructosyl carbocation and not the protonation of the glycosidic oxygen.…”
Section: Resultsmentioning
confidence: 96%